Study Literatur: Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan - Sari, Regi Regita; Ariyani, Risma; Amanda, Melinda; Sulaeman, Eman (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Organizations can change their management patterns through transformational leadership to improve optimal performance, especially when facing increasingly complex competition. Human resources, with their unique ideas and mindsets, are an important key in implementing the organization's vision, goals, and objectives. Employees play a vital role in achieving organizational success through their contributions. Employee performance is an important indicator that organizations must consider. Leaders play a major role in creating a positive work environment, and transformational leadership is one of the most popular styles, especially in the digital age. With secondary data collected from relevant articles, this journal uses a literature review method to investigate the effect of transformational leadership on employee performance. Research findings show that transformational leadership style significantly affects employee performance. Employees who actively participate feel more motivated, confident, and committed to following the organization's philosophy, ideology, and vision. Interesting changes more easily influence them and show high dedication while realizing their potential. Employees who are inspired by transformational leadership tend to work harder, improve performance, and display helpful behaviors, which ultimately support organizational growth.